2015
DOI: 10.1515/aucts-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Aspects Regarding The Organizational Stress Analysis

Abstract: This work presents a research of methodology in occupational stress analyse in the educational field, as a part of a larger study. The objectives of the work are in finding accents in existence of significant relations between stressors and effects, meaning the differences between the indicators of occupational stress to teaching staff in primary and gymnasium school, taking notice of each specific condition: the institution as an entity, the working community, the discipline he/she is teaching others, the geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This study aims to establish a model of projects as a source of stress at work through a systematic literature review and a thematic analysis using the established Cooper and Marshall (1976) workplace stress model. The Cooper and Marshall (1976) model of stress at work has been adopted as a form of analysis by many empirical studies (Lai et al , 2015; Irimie et al , 2015; Cusack, 1982; Botts, 1986; Wilson, 1988; Yu, 1996; Allison, 1995). Beyond project management other studies have also used the systematic review method when applying the Cooper and Marshall (1976) model of stress at work to their particular domain.…”
Section: Methodsmentioning
confidence: 99%
“…This study aims to establish a model of projects as a source of stress at work through a systematic literature review and a thematic analysis using the established Cooper and Marshall (1976) workplace stress model. The Cooper and Marshall (1976) model of stress at work has been adopted as a form of analysis by many empirical studies (Lai et al , 2015; Irimie et al , 2015; Cusack, 1982; Botts, 1986; Wilson, 1988; Yu, 1996; Allison, 1995). Beyond project management other studies have also used the systematic review method when applying the Cooper and Marshall (1976) model of stress at work to their particular domain.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported differences in these risk factors, which may occur due to geographical area, diet and other factors. In Romania, one such study was carried out in Brasov city [11].…”
mentioning
confidence: 99%